Design and construction of cuttlefish ink derived melanin complexed microneedles for microenvironment regulation to improve vitiligo treatment - Weimiao Li; Yan Shi; Ruimin Zhan; Lu Liu; Jiarui Wang; Minhyeock Lee; Bingqiang Zhang; Shaoshuai Liang; Zhiguo Wang; Ming Kong (Marine Life Science & Technology, 2025)
Vitiligo is an autoimmune disorder marked by melanocyte destruction and epidermal depigmentation, primarily driven by inflammatory and oxidative stress within the affected skin lesions. Consequently, there is an urgent need for therapeutic strategies focused on protecting melanocytes and replenishing melanin for effective vitiligo management. In this study, a novel microneedle-based therapeutic platform (C/D/E@MN) was fabricated that was composed of cuttlefish ink nanoparticles (CINPs) for melanin supplementation, dipotassium glycyrrhizinate (DPG) for inflammation regulation, and skin-derived exosomes (EXO) to promote melanocyte proliferation. In addition, microneedles with varying dissolution profiles (swellable, slow-dissolving, and fast-dissolving) were designed and evaluated their performance to optimize therapeutic efficacy. In vitro results demonstrated that fast-dissolving microneedles (FDMN) significantly reduced cellular reactive oxygen species (ROS) and the secretion of vitiligo-related inflammatory cytokines and chemokines, such as IL-8, CXCL-16, and HMGB-1. Upon a vitiligo mice model, C/D/E@FDMN treatment group generated a significant increase in skin melanin content and a 15.5% reduction of whitening degree. The microneedles protected melanocytes and promoted lesion repigmentation through synergistic antioxidant, anti-inflammatory and cyto-proliferative mechanisms, offering a promising strategy for improved vitiligo therapy.